College students with a movie camera: How they may be motivated to learn by themselves? - Beaufils, A.-F.; Haddad, Samir R.; Oliveira, A. (ICERI2016 Proceedings, 2016)
The rapid progress of Information and Communication Technologies (ICT) we have witnessed in recent years has changed the way we learn, communicate, collaborate and share information. Group work as well as any type of active participation in society – particularly in what concerns digital citizenship –, has become more affordable and easier thanks to software, multimedia, social media, internet, networking and online collaboration tools, that promote interaction even among geographically dispersed people. Knowing how to use these technologies in training activities, teaching and learning in an appropriate and productive way is one of our major challenges. Contemporary students do use ICT for the most different purposes, in all their personal activities. Since they somehow rely on computers and virtual realities to drive their lives, they tend to lose their motivation when attending traditional expositive classes in which they have a passive role. This paper presents a case-study conducted with a population of 32 Portuguese and Spanish students, from three courses: Physiotherapy, Nutrition Science and Nursing, in a Portuguese University. This experience occurs in a context where these college students (from the first to the third year) are learning English, one of the subjects in health courses. In this case, the teacher was facing a challenge: what would be the most appropriate teaching method that could allow all of them, no matter their level of proficiency in English and their course, to learn new vocabulary in their specific field and gain more self-confidence when communicating in English? It was a 45-hour classroom tuition curricular unit during a semester. Digital technologies were used to promote students’ involvement and collaboration, a framework that could be proposed for English teaching, using ICT, in this case a digital camera, in various learning environments, whether formal or informal. In sum, we wanted to verify to what extent the involvement of participants regarding the use of ICT, when they are given the chance to be creative in a student-centered teaching, through the exclusive use of technological devices and digital resources (no printed material), promotes their knowledge and learning process. The present experience involved a project that consisted in setting up a health centre to serve English-speaking patients in Portugal. Students had to work together preparing workshops and health check-up sessions. Students filmed all classes and prepared a video showing how the health centre would work and what it would offer. Between classes, they used a Moodle e-learning platform to communicate, upload contents and develop the project. Their videos and inputs in the platform were subsequently assessed. As expected, students not only gained confidence in English, but also acquired multimedia skills and empowerment. Since language skills allow people to communicate, study, work, travel and enlarge their knowledge, they have become important elements of active citizenship. Therefore, this case-study could be generalized to other situations and converted into a methodology for English classes, for instance, to be used in digital inclusion programmes for poor populations – in Brazil such courses are run by “Telecentros”, which are equipped with computers, internet and cameras, to offer computer-science and English classes, so students may gain new competences also as digital citizens in our global English-speaking world.